2003
DOI: 10.1097/01.asn.0000077411.98742.54
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Matrix Remodeling in Diabetic Kidney

Abstract: Abstract. Excessive deposition of extracellular matrix (ECM) in the kidney is the hallmark of diabetic nephropathy. Although the amount of ECM deposited in the kidney depends on the balance between the synthesis and degradation of ECM, the role of ECM degradation in matrix remodeling has been less well appreciated. High glucose, advanced glycation end products, angiotensin II, and TGF-␤1 all increase intracellular reactive oxygen species (ROS) in renal cells and contribute to the development and progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 31 publications
2
100
0
Order By: Relevance
“…Increased ROS generation can induce cell inflammation (20,21). The present study conducted on isolated rat glomerular endothelial cells demonstrated that the expression of p47 phox protein, one of the NAD(P)H oxidase subunits, was increased by Ang II treatment according to the increased ROS generation.…”
Section: Discussionmentioning
confidence: 63%
“…Increased ROS generation can induce cell inflammation (20,21). The present study conducted on isolated rat glomerular endothelial cells demonstrated that the expression of p47 phox protein, one of the NAD(P)H oxidase subunits, was increased by Ang II treatment according to the increased ROS generation.…”
Section: Discussionmentioning
confidence: 63%
“…1,49 A large body of evidence indicates that ROS have a major role in the development of diabetic nephropathy. [50][51][52] TXNIP binds to the active cysteine residue of thioredoxin (TRX) and inhibits its antioxidative function. Hence, the TRX/TXNIP system has a major role in regulation of cellular redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, renal tubular cells, in response to injury or local activation, lose their epithelial phenotype and acquire profibrotic features that are characteristic of mesenchymal cells (4). EMT is regulated by several growth factors and cytokines, including TGF-␤1, Fibroblast growth factor, IL-1, EGF, and angiotensin II (5)(6)(7)(8)(9). In addition, we previously reported that advanced glycation end products (AGE) also may induce EMT, via activation of the receptor for AGE (RAGE), potentially contributing to their profibrotic actions (3).…”
mentioning
confidence: 99%